2021
DOI: 10.1097/mat.0000000000001539
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation Support for Antineutrophil Cytoplasmic Antibody-associated Vasculitides: An ELSO Registry Analysis

Abstract: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides with pulmonary involvement include granulomatosis with polyangiitis, microscopic polyangiitis, and eosinophilic granulomatosis with polyangiitis, and can present with life-threatening pulmonary hemorrhage in up to 40% of patients. Mortality in those patients who require intubation and mechanical ventilation can reach 77%. Extracorporeal membrane oxygenation (ECMO) can be used to support these patients through definitive diagnosis and treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Supporting these patients with VV-ECMO ensures sufficient time to make a definite diagnostic and initiate treatment measures, along with minimizing ventilator-associated lung injury. The Extracorporeal Life Support Organization's registry of patients with AAV on ECMO showed a 73% survival rate, and factors associated with death included an older age, use of venoarterial ECMO, ECMO-cardiopulmonary resuscitation, and sustaining cardiac arrest before ECMO ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting these patients with VV-ECMO ensures sufficient time to make a definite diagnostic and initiate treatment measures, along with minimizing ventilator-associated lung injury. The Extracorporeal Life Support Organization's registry of patients with AAV on ECMO showed a 73% survival rate, and factors associated with death included an older age, use of venoarterial ECMO, ECMO-cardiopulmonary resuscitation, and sustaining cardiac arrest before ECMO ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have described the benefits of performing venovenous-extracorporeal membrane oxygenation (VV-ECMO) for severe respiratory failure from DAH associated with AAV ( 3 , 4 ). During ECMO, patients receive anticoagulants that help prevent thrombotic complications and maintain circuit patency, placing them at the risk of bleeding ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“… 64 Veno-arterial ECMO is a suitable treatment option for poisoning cases complicated by refractory cardiogenic shock or cardiac arrest, offering high survival rates with low complications. 65 Extracorporeal membrane oxygenation may be indicated in severe status asthmaticus, 66 pheochromocytoma-induced cardiomyopathy, 67 , 68 fulminant myocarditis, 69 ANCA-associated vasculitis, 70 and refractory thyroid storm. 71 …”
Section: Indicationsmentioning
confidence: 99%
“…Children with DAH had higher mortality on ECMO (37%) than adults with DAH (17%). The authors concluded that venovenous ECMO should be used as needed [57].…”
Section: Extracorporeal Membrane Oxygenation Supportmentioning
confidence: 99%